LEADERSHIP OF PUBLIC OFFICIALS (A STUDY OF THE IDEAL LEADERSHIP OF THE REGENT OF GOWA DISTRICT, SOUTH SULAWESI PROVINCE) - Husnul Haerati; Muh Nur Yamin; Haedar Akib (Universitas Negeri Makassar, 2026)
Administration and management are processes, occurring within the organization. While the core of management and administration is leadership. Leadership is the determinant of whether an organization runs well or not. One of the leaders who is considered qualified or ideal is Adnan Purichta ihsan, the Regent of Gowa Regency. This study aims to identify and describe the leadership of the Regent of Gowa Regency based on the principles of the relevant 5 pillars of leadership theory. The method used in this research is qualitative. While the type of research used is the appropriate case study method proposed by Robert K Yin. The data collection techniques used in this research are interviews, and documentation. The data validity technique used in this research is triangulation. The results showed that the leadership of the Regent of Gowa Regency can be said to be ideal leadership. There are 5 requirements to be a quality leader. Namely power, competence, credibility, willingness and enthusiasm, and courage. From these five conditions, it is found that the Regent of Gowa Regency fulfills the five conditions to become a quality leader. Although there is no perfect leadership, the five conditions are fulfilled, so the result is that the Regent of Gowa Regency is an ideal leader. This is in line with the quality leader proposed by Augustine Johanes Djohan. Quality leaders and ideal leadership have a close and interrelated relationship where quality leaders are individuals who demonstrate leadership qualities and characteristics that are considered positive as well as effective, while ideal leadership reflects the highest standards or expectations in the context of leadership.